Enhanced recovery after surgery protocol versus conventional care in emergency abdominal trauma surgery: a prospective, randomised, controlled study - Dhiman, Ajay Kumar; Jagne, Nilesh; Uniyal, Madhur; Kumar, Ajay; Azam, Quamar (International Surgery Journal, 2021)
Background: Since 1990s there has been a defined role of ERAS in elective surgeries, to optimize the peri-operative care, reducing post-operative complications and length of stay and hence, the overall costs. However, there is paucity of literature in its effectiveness in emergency trauma surgeries. The aim of the study was to investigate the feasibility and outcomes of ERAS protocol in emergency abdominal surgery in the setting of trauma. Methods: Institutional IEC approved study. A prospective randomized of 52 patients with abdominal trauma undergoing emergency laprotomy were included in the study and divided into two groups: ERP and conventional group. The ERP included early feeding, early urinary catheter removal, early mobilization/physiotherapy, early intravenous line removal and early optimal oral analgesia. The primary end-points were the length of hospital stay and secondary end-points included complication rate and re-admission rate. Results: The two groups were comparable with regards to age, gender, mechanism of injury and ISS score. Hospital stay was significantly shorter in the ERAS group: 4.67 days verses 13.36 days (p<0.001). There were 15 and 11 complications in the control and study group respectively. When graded as per the Clavien-Dindo classification there was no significant difference in the 2 groups (p=0.306). Conclusions: This study shows that early recovery programs can be successfully implemented with significant shorter hospital stays without any increase in postoperative complications in trauma patients undergoing emergency laparotomy for abdominal trauma.